Impact of coexisting diabetes on the development of cardiovascular disease and death in patients with cancer - Yoshihiro Kuwabara; Toshitaka Morishima; Haruka Kudo; Mizuki Shimadzu Kato; Shihoko Koyama; Kayo Nakata; Isao Miyashiro (PLoS ONE, 2026)
Diabetes is a risk factor for the development of cardiovascular disease (CVD); however, its effects on the incidence of CVD and survival in patients with cancer without CVD at the time of cancer diagnosis remain unclear. Population-based information was obtained from the Osaka Cancer Registry linked to administrative data, and the impact of diabetes at cancer diagnosis on overall survival and the development of CVD in patients without CVD at cancer diagnosis was analyzed using Cox proportional hazards models. A total of 121,997 patients diagnosed with cancer but without CVD in Osaka Prefecture, Japan, between 2010 and 2015 were included in the analysis. Of these, 4,317 patients had diabetes at the time of cancer diagnosis. The presence of coexisting diabetes was associated with increased risks of all-cause mortality (adjusted hazard ratio: 1.40 [95% confidence interval: 1.33–1.48]) and development of CVD (1.37 [1.28–1.46]), compared with the absence of coexisting diabetes. For 21,292 patients with a record of hospitalization within 2 months prior to death, the estimated cause of death was tabulated. In all, 899 (4.6%) and 111 (6.9%) patients in the no-coexistent diabetes and coexistent diabetes groups, respectively, died from circulatory disease. In patients with cancer without CVD at cancer diagnosis, coexisting diabetes may increase the risk of developing CVD and affect survival.